2019
DOI: 10.7150/jca.33765
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1 Promotes Vasculogenic Mimicry in Gastric Cancer by Upregulating EMT Signaling

Abstract: Background: Galectin-1 (Gal-1) expression was positively associated with vasculogenic mimicry (VM) in primary gastric cancer (GC) tissue, and that both Gal-1 expression and VM in GC tissue are indicators of poor prognosis. However, whether Gal-1 promotes VM, and by what mechanismsremains unknown.Methods: To investigate the underlying mechanisms,wound healing assay, proliferation assay, invasion assay, and three-dimensional culture were used to evaluate the invasion, metastasis and promoted VM formation effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…IHC was performed using lung tissues. Primary antibodies recognizing TGF-β1(dilution, 1:200), JAK2 (dilution, 1:200) , p-JAK2 (dilution, 1:100), STAT3 (dilution, 1:200), or p-STAT3 (dilution, 1:200) were incubated with tissue slides overnight at 4 C, and then processed according to our previous report [35]. All staining was imaged digitally using the same light exposure and evaluated using Image Pro Plus (IPP), a digitalized IHC scoring program (Media Cybernetics, San Diego, CA, USA).…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
“…IHC was performed using lung tissues. Primary antibodies recognizing TGF-β1(dilution, 1:200), JAK2 (dilution, 1:200) , p-JAK2 (dilution, 1:100), STAT3 (dilution, 1:200), or p-STAT3 (dilution, 1:200) were incubated with tissue slides overnight at 4 C, and then processed according to our previous report [35]. All staining was imaged digitally using the same light exposure and evaluated using Image Pro Plus (IPP), a digitalized IHC scoring program (Media Cybernetics, San Diego, CA, USA).…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
“…Roswell Park Memorial Institute (RPMI) medium (Thermo Fisher Scienti c, Waltham, MA, USA) was used to culture the cells, The culture medium was supplemented with 10% (V/V) fetal bovine serum (FBS; Thermo Fisher Scienti c), 100 U/mL penicillin and 100 mg/mL streptomycin (Gibco, Grand Island, NY, USA). The cells were maintained at 37 °C in a humidi ed atmosphere containing 5% (V/V) CO 2 [24] When con uence reached 80%, the cells were passaged via trypsinization.…”
Section: Cell Line and Cell Culturementioning
confidence: 99%
“…Lentiviral transduction was performed as previously described [24] . Lentiviral vectors for LGALS1 overexpression and silencing were constructed by Genechem Co. Ltd (Shanghai, China).…”
Section: Lentiviral Transductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maniotis reported that VM was an endothelial-independent vascular channel that contained red blood cells, formed with highly aggressive and metastatic cancer cells in 1999. The structure of VM was a lack of endothelial cells in the internal lining, with CD34 immunohistochemical staining negative/Periodic acid-Schiff (PAS) histochemical staining positive [46]. Furthermore, CSCs possess the highest plasticity and may transdifferentiate to ECs by EMT induction.…”
mentioning
confidence: 99%